PENGARUH RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT BANK CENTRAL ASIA TBK PERIODE 2012-2023 - Sari, Novita; Suraya, Amthy (Journal of Research and Publication Innovation, 2024)
This study aims to find out how much Return On Equity (ROE) and Earning Per Share (EPS) affect the Share Price of PT Bank Central Asia Tbk. for the 2012-2023 period. The method used in this study is a quantitative method. The population of this study is the published financial statements of PT Bank Central Asia Tbk. Sampling uses the purpose sampling technique. The sample of this study is financial statements in the form of financial position statements, profit and loss statements, and stock prices for the 2012-2023 period. The data analysis methods used were classical assumption test, simple linear regression analysis, multiple linear regression analysis, Coefficient of Determination (R2) and hypothesis testing t-test, F-test using the SPSS 26 approach. The results of the t-test show that ROE has a significance value (0.006 < 0.05) and a t-value calculated > t table (-3.296 > 2.262), this means that ROE partially has a negative and significant effect on the stock price. EPS has a significance value (0.067 < 0.05) and a t-value < t table (-2.047 < 2.262), this means that EPS has no effect on the stock price. Meanwhile, the results of the F-Test show that the significance value (0.016 < 0.05) and the F value of the table > F calculation (5.687 > 4.26), this means that ROE and EPS simultaneously affect the stock price. The results of the determination coefficient (R2) test showed an Adjusted R-Square value of 0.513, meaning that together the influence of ROE and EPS on stock prices contributed 51.3% and the remaining 48.7% was influenced by other variables that were not studied in this study.